Integrasi Pembelajaran Multi Metode melalui Metode Story-Telling: Metode Pengajaran Nabi Muhammad SAW yang Efektif Sepanjang Zaman - Isya', Muhammad Andi (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2020)
The academic success of students is very dependent on the quality of teachers, the quality of teaching and learning interactions depends on the intention of teacher teaching activities and the intention of student learning activities including the use of models, methods, techniques, and learning media. The success of a learning strategy depends on the expertise of the teacher in using learning models, methods, techniques, and media. Because each teacher has different knowledge, experience, abilities, views and teaching styles. However, all models, methods, techniques, and learning media have been exemplified by the Prophet Muhammad SAW. This article aims to describe multi-method learning through the Story-Telling method that was taught, exemplified and practiced by the Prophet Muhammad and its effectiveness to this day. This research is a qualitative literature study. The approach used is the empirical historical approach because the historical approach must be understood as a type of empirical, empirical approach, especially in the sense where this term is contrasted with an apriorist, rationalistic, or intellectualist orientation. Reflexive methods such as narrative inquiry, autoetnography, joint ethnography, and community dialogue methods. As a form of understanding, narrative inquiry helps us shape our understanding of complex world events. From the results of the discussion it can be concluded as follows: 1) In Islam, the method of telling stories (story-telling) cannot be equated with the method of storytelling, even though storytelling is aimed at educating. It is dry with Islamic values ??(Aqidah and morals). 2) The storytelling method is taught, exemplified by the Prophet Muhammad SAW's practice of containing the best story content, to strengthen the heart (motivation). 3) The storytelling method in Islam is integral from the linguistic aspect: storytelling, brainstorming, publication and recording; from a mathematical aspect: calculation, classification, reasoning, heuristic, socratic; from the spatial aspect: visualization, color, pictures, graphics, sketches; from the musical aspect: rhythm, concept, supermemory, discography. from the kinesthetic aspect: response, conception, hans-on, theater map; from the interpersonal aspect: sharing feelings, sculpture formation; teamwork, simulations, boar games; from the intra-personal aspect: reflection, feeling, self-experience, formatting goals; timming; from natural aspects: walks, decoration, fauna, eco studies, outside windows.